A Facile Way for Acquisition of a Nanoporous Pt–C Catalyst for Oxygen Reduction Reaction. Issue 12 (24th May 2021) - Xie, Xianxian; Khalakhan, Ivan; Vorokhta, Mykhailo; Yakovlev, Yurii; Dinhová, Thu Ngan; Nováková, Jaroslava; Kúš, Peter; Dopita, Milan; Veltruská, Kateřina; Matolínová, Iva
Abstract: Here, the concept of preferential leaching of cerium oxide on ternary Pt–C–CeO2 compound is demonstrated in order to develop a cost‐effective catalyst for the cathode in proton exchange membrane fuel cells. The Pt–C–CeO2 thin film catalyst is prepared by simultaneous magnetron co‐sputtering of Pt, C, and CeO2 . The morphology, structure, and composition of the Pt–C–CeO2 layer are characterized by transmission electron microscopy, scanning electron microscopy, energy dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and X‐ray diffraction. Both half‐cell and single‐cell tests are performed to determine its activity and durability. During an activation electrochemical cycling procedure, CeO2 is leached from the compound, leaving behind a porous Pt–C matrix which exhibits almost 3 times higher electrochemically active surface area in comparison with pure Pt with identical loading before and even after accelerated degradation tests in the half‐cell. When used as the cathode in a single‐cell membrane electrode assembly, decomposed Pt–C–CeO2 also shows greater power density than pure Pt. Abstract : The preparation of porous Pt–C catalyst by dealloying Pt–C–CeO2 thin film prepared by simultaneous magnetron co‐sputtering is reported. The catalyst displays high activity as both proton exchange membrane fuel cell cathode and anode.